Virtual Simulation Games in Entrepreneurship Education : Status Quo and Prospects - Sziegat, Hongmei (United Kingdom, 2025)
This study reviews the current status and future perspectives of virtual simulation games in entrepreneurship education in higher education institutions. Virtual simulation games act as digital twins to replicate real-world scenarios, which can be integrated as a part of online learning in entrepreneurship courses or digital learning resources in entrepreneurship education in higher education institutions. Virtual simulation games as digital tools for specific learning tasks or teaching methods engage students with virtual simulation learning experiences to generate improved student learning in immersive and interactive environments through the use of extended reality (XR) including virtual reality (VR), augmented reality (AR), and mixed reality (MR) in a virtual or blended learning environment. This study indicates the promising development of AI and XR applications in virtual simulation games in entrepreneurship education. It provokes discussions on the technological, pedagogical, and content design of virtual simulation games and their integration into hybrid and online models of entrepreneurship education, which has significant implications for the digital transformation and innovation of entrepreneurship education in higher education institutions. It draws attention to digital well-being and digital inclusion in virtual simulation game-based learning in entrepreneurship education in higher education institutions.
Proceedings of the 18th European Conference on Games Based Learning